THE MASS-DEPENDENCE OF ANGULAR MOMENTUM EVOLUTION IN SUN-LIKE STARS - Matt, Sean P.; Brun, A. Sacha; Baraffe, Isabelle; Bouvier, Jérôme; Chabrier, Gilles (Astrophysical journal. Letters, 2015)
To better understand the observed distributions of the rotation rate and magnetic activity of Sun-like and low-mass stars, we derive a physically motivated scaling for the dependence of the stellar wind torque on the Rossby number. The torque also contains an empirically derived scaling with stellar mass (and radius), which provides new insight into the mass-dependence of stellar magnetic and wind properties. We demonstrate that this new formulation explains why the lowest mass stars are observed to maintain rapid rotation for much longer than solar-mass stars, and simultaneously why older populations exhibit a sequence of slowly rotating stars, in which the low-mass stars rotate more slowly than solar-mass stars. The model also reproduces some previously unexplained features in the period-mass diagram for the Kepler field, notably: the particular shape of the "upper envelope" of the distribution, suggesting that ~95% of Kepler field stars with measured rotation periods are younger than ~4 Gyr; and the shape of the "lower envelope," corresponding to the location where stars transition between magnetically saturated and unsaturated regimes.